Short term administration of glucocorticoids in patients with protracted and chronic gout arthritis. Part III – frequency of adverse events - A A Fedorova; V G Barskova; I A Yakunina; V A Nasonova (Научно-практическая ревматология)
Objective. To assess frequency of adverse events during short term administration of gluco- corticoid (GC) in protracted and chronic gout arthritis. Material and methods. 59 pts with tophaceous gout (crystal-verified diagnosis) and arthritis of three and more joints lasting more than a months in spite of treatment with sufficient doses of nonsteroidal anti-inflammatory drugs were included. Median age of pts was 56 [48;63], median disease duration – 15,2 years [7,4;20], median swollen joint count at the examination – 8 [5;11]. The patients were randomized into 2 groups. Methylprednisolone (MP) 500 mg/day iv during 2 days and placebo im once was administered in one of them, betamethasone (BM) 7 mg im once and placebo iv twice – in the other. Clinical evaluation of inflamed joints was performed every day. Standard laboratory examination and ECG were done before drug administration, at 3rd, 7th, and 14th day of follow up. Immunoreactive insulin level was evaluated before drug administration and at day 14. Blood pressure (BP) was measured every day. Results. After first GC administration BP elevated in 28 (47%) pts. In pts not having appropriate BP values BP elevated in 73% of cases. Pts with appropriate BP values showed less frequent BP elevation – 38% (p=0,02). In 8 (13%) pts at day 3 after GC administration ECG signs of myocardial blood supply deterioration were revealed. Glucose level elevated in 10 (17%) pts and after the second BM administration – in 5 (8%) pts. Cholesterol level did not significantly change after 14 days of follow up but in 28 (47%) pts it increased in comparison with baseline. Trigliceride level significantly decreased at day 14 from 149 [106; 187] to 108 [66,5; 172] mg/dl (p=0,02). 26 (44%) pts had face hyperemia, 4 (7%) –42 palpitation and 2 (3,4%) – bitter taste. Conclusion. Administration of short course of GC in pts with gout requires monitoring of possible adverse events. Antihypertensive therapy providing appropriate BP level decreases frequency of BP elevation.